The role of coaches of wheelchair rugby in the development of athletes with a spinal cord injury - Tawse, H.; Bloom, G. A.; Sabiston, C. M.; Reid, G. (Qualitative Research in Sport, Exercise and Health, 2012)
Wheelchair rugby allows individuals living with quadriplegia to compete in an elite-level sport. It is currently one of the fastest-growing disability sports in the world and is the only full contact sport played by athletes with a disability. The purpose of this study was to explore the personal experiences of wheelchair rugby coaches in the development of their athletes who had entered their sport after acquiring a spinal cord injury. Four elite wheelchair rugby coaches were interviewed using a semi-structured guide. Data collection and analyses followed an interpretative phenomenological approach. Participants discussed the myriad of roles they carried out as wheelchair rugby coaches and the diverse range of their coaching responsibilities. They also alluded to their philosophies in both the personal and athletic development of their athletes and the unique strategies they utilised with them. The results highlight the important role of a coach in facilitating athlete development in disability sport.